Safety and efficacy of l‐tryptophan produced with Escherichia coli CGMCC 11674 for all animal species. (21st March 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on l ‐tryptophan produced by fermentation with Escherichia coli CGMCC 11674 when used as a nutritional additive in feed and water for drinking for all animal species and categories. The production strain did not raise safety concerns. The FEEDAP Panel cannot conclude on the safety of l ‐tryptophan produced by E. coli CGMCC 11674 for the target species and for the consumer due to the tryptophan‐related impurities such as 1, 1'‐ethylidene‐bis‐l ‐tryptophan (EBT). The FEEDAP Panel has concerns on the safety of the simultaneous oral administration of l ‐tryptophan via water for drinking and feed. Using unprotected forms of tryptophan in ruminants can be a risk. The FEEDAP Panel cannot conclude on the dermal or ocular irritation and skin sensitisation of l ‐tryptophan produced by E. coli CGMCC 11674. The additive poses a risk by inhalation from the exposure to endotoxins for people handling the additive. The use of l ‐tryptophan produced by E. coli CGMCC 11674 in animal nutrition does not pose a risk to the environment. The additive under assessment is regarded as an effective source of the amino acid l ‐tryptophan for all non‐ruminant species. If the product l ‐tryptophan is intended for use in ruminants, it should be protected from ruminal degradation.